Pre-service Mathematics Teachers' Professional Competency Development Through Analysis of Learning Obstacles - Mohamad Gilar Jatisunda; Dede Salim Nahdi; Ujiati Cahyaningsih; Dela Rohimatunnisa (EduMa: Mathematics education learning and teaching, 2022)
It is the role of teachers to increase the quality of learning. When the instructor wants to increase the quality of learning, reflective practice is an option. However, instructors' current practice of learning reflection is based only on classroom action research and is primarily concerned with enhancing learning models rather than paying attention to student replies. As a result, prospective mathematics teachers must be able to engage in reflection techniques based on didactical design research that emphasizes student reactions. This study employs a descriptive qualitative technique, with the subjects being Mathematics Education students at the University of Majalengka who are enrolled in the Kapita Selekta Mathematics course. Students experience translating scientific, mathematical knowledge into mathematics ready to be taught in schools based on the study findings. Every step in the process of becoming a mathematics teacher has an impact on pedagogical content understanding